Regenerative Rehabilitation: Applied Biophysics Meets Stem Cell Therapeutics - Rando, Thomas A. (Cell Stem Cell, 2018)
The emerging field of regenerative rehabilitation integrates biological and bioengineering advances in regenerative medicine with rehabilitative sciences. Here we highlight recent stem cell-based examples of the regenerative rehabilitation paradigm to promote tissue repair and regeneration, and we discuss remaining challenges and future directions for the field.